Characterization of acute respiratory infections behavior. Cienfuegos Province. First quarter 2020 - Bárbara del Rosario Téllez Cacín; María Lina Valdés Gómez; José Aurelio Díaz Quiñones; Lourdes Elena Duany Badell; Ling Denisse Santeiro Pérez; Sadys Suarez del Villar Seuret (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: due to the current pandemic of COVID 19, it is important to know the categorizing essentialities of acute respiratory infections in general for future studies in which COVID 19 will constitute a category of the taxonomy of those to be taken into account. Objective: to characterize acute respiratory infections in the Cienfuegos province from January 1 to March 31, 2020. Methods: the population studied was the population of the Cienfuegos province. The main study variables considered were: age groups, municipalities of residence, demand for medical consultations, statistical weeks, rates temporal variation, their trend, severity of clinical evolution, admissions and deaths from severe respiratory infections, outbreaks and epidemiological surveillance. Statistical methods and techniques used were, from descriptive statistics: absolute and relative frequencies, means, rates, increases and decreases in rates, the endemic corridor and its trend. Results: the characterizing essentialities were: its highest incidence in children under five years of age and adults 60 years and over; the leading cause of death was from community-acquired pneumonia; the identified circulating viruses were respiratory syncytial, parainfluenza, unsubtyped influenza A, and coronavirus. The trend is upward. Conclusions: the behavior of acute respiratory infections was within the expected parameters, except that from week eleven there was an increase in medical care, which could be related to the inquiring and surveillance actions.